The Vision Zero Handbook Theory, Technology and Management for a Zero Casualty Policy - Edvardsson Björnberg, Karin; Belin, Matts-Åke; Hansson, Sven Ove; Tingvall, Claes (Springer International Publishing : Imprint: Springer, 2020)
This handbook provides a comprehensive treatment of Vision Zero, an innovative policy on public road safety developed in Sweden. Covering all the major topics of the subject, the book starts out with a thorough examination of the philosophy, ideas and principles behind Vision Zero. It looks at conditions for the effectiveness of the policy, principles of safety and responsibility as well as critique on the policy. Next, the handbook focuses on how the Vision Zero ideas have been received and implemented in various legislations and countries worldwide. It takes into account the way Vision Zero is looked at in the context of international organizations such as the WHO, the UN, and the OECD. This allows for a comparison of systems, models and effects. The third part of the handbook discusses the management and leadership aspects, including ISO standards, equity issues, other goals for traffic and transportation, and opportunities for the car industry. Part four delves into tools, technologies and organizational measures that contribute to the implementation of Vision Zero in road traffic. Examples of specific elements discussed are urban and rural road designs, human factor designs, and avoiding drunk and distracted driving. The final part of the handbook offers perspectives on the transfer of Vision Zero policy to other areas, ranging from air traffic to suicide prevention and nuclear energy. Vision Zero is a public road safety policy including both a long-term goal that no one shall be killed or seriously injured as a consequence of accidents in road traffic and a safety principle stating that the design and function of the road transport system shall be adapted to meet the requirements that follow from that goal. It is a new road safety paradigm which has resulted in new types of responsibilities among stakeholders, technological innovations, and new strategies and organizational measures to achieve a safe system. The road safety work based on Vision Zero has shown promising results, and although Sweden has not yet reached a safe system, the number of fatalities and severe injuries has decreased substantially.